The emergence of penicillin resistance in nasopharyngeal and oral isolates of streptococcus pneumoniae and viridans streptococci following beta-lactam antibiotic exposure - Van Den Berg, Ingrid Susan (My University, 1990)
Increasing levels of penicillin-resistant Streptococcus pneumoniae and viridans streptococci are becoming a major cause for concern, particularly in South Africa. To investigate this problem 100 paediatric patients, admitted to Baragwanath Hospital during the period April to July 1988, were swabbed nasopharyngeally and orally. On admission 24 out of 53 (45%) pneumococcal carriers carried penicillin-resistant strains, while on discharge 33 strains out of 45 (73%) were penicillin-resistant (p = 0.003). The corresponding figures for high level penicillin-resistant strains were 7 out of 53 (13%) on admission to 20 out of 45 (44%) on discharge (p = 0.001). Treatment with 3-lactam antibiotics reduced the pneumococcal carriage rates by eliminating penicillin-susceptible strains while many children who were not carriers on admission became carriers of penicillin-resistant strains during hospitalisation. In the case of penicillin-resistant viridans streptococci in the oral cavity the use of 8-lactam antibiotics was accompanied by significant increases in both penicillin-resistant and high level resistant strains.
Submitted in fulfilment of the conditions for the degree of Master of Science in Medicine, in the Faculty of Medicine, University of the Witwatersrand, Johannesburg. June 1990
Keywords: Penicillin Resistance; Nasopharynx; Streptococcus pneumoniae; Viridans Streptococci; Monobactams